Expression of CD69 antigen on synovial fluid T cells in patients with rheumatoid arthritis and other chronic synovitis. Issue 6 (June 1993) - Afeltra, A; Galeazzi, M; Ferri, G M; Amoroso, A; De Pità, O; Porzio, F; Bonomo, L
Abstract : OBJECTIVES--The expression of the CD69 antigen on synovial fluid and peripheral blood lymphocytes was studied in 12 patients with rheumatoid arthritis (RA), five subjects with other forms of chronic synovitis, and on the peripheral blood lymphocytes of 15 patients with systemic lupus erythematosus (SLE) and immune vasculitis. METHODS--The CD69 antigen and other activation markers (HLA-DR, interleukin 2 receptor (IL-2R), transferrin receptor) were measured by cytometric analysis. In patients with RA soluble IL-2R was determined by enzyme linked immunosorbent assay (ELISA). RESULTS--The percentage of T cells bearing CD69 was significantly increased in synovial fluid from patients with RA (30.3 (13)%) and other chronic synovitis (18 (9)%). The expression of CD69 on peripheral blood lymphocytes of patients with RA, other chronic synovitis, and SLE and immune vasculitis was within the normal range 2.1 (1.2)%. According to previously published work, a high proportion of synovial fluid T cells are HLA-DR positive (64.2 (12.4)% in synovial fluid from patients with RA and 61 (1.2)% in synovial fluid from patients with other chronic synovitis). Transferrin receptor expression on synovial fluid was up-regulated compared with that on peripheral blood. The increase of IL-2R expression on synovial fluid lymphocytes v peripheral blood was not significant; the quantitative determination of soluble IL-2R levels gave a mean value of 921 (351) U/ml in synovial fluid of patients with RA, 672 (229) U/ml in the serum of the same patients, and 273 (100) U/ml in serum from normal subjects. CONCLUSIONS--Synovial fluid lymphocytes are in a different functional state than peripheral blood lymphocytes. CD69 antigen is an interesting cellular marker which should be studied in patients with chronic synovitis. The unusual expression of the activation antigens and the sequence of their appearance require further study.